Minimasi Jalur Distribusi di PT. XYZ dengan Metode Improved Cluster First Route Second - Chandra, Agung; Setiawan, Bambang (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2019)
Reducing distance in delivery service from distribution center to subsidiaries can be reached through well-managed routing which known as VRP - Vehicle Routing Problem. This study was conducted in a food industry PT. XYZ. Two methods, Cluster First Route Second algorithm and linier programming were used to obtain the minimum distance between distribution center to outlets in Jabodetabek area. The cluster first route second method was improved using linier programming – solver. The improved method shows 774.18 kilometer is better than Cluster Firs Route Second, 832.19 kolometer which is 6.97% shortened.